Comparison of gnostic and balancing capabilities in different sport disciplines - Zuzana Frčová; Veronika Flosniková (Matej Bel University, 2021)
Background: The quality of proprioception, which we classify as Gnostic functions, affects a person's physical performance. Sports performance requires a good perception of one's own body, a sufficient ability to control one's body and keep it as stable as possible in space. The purpose: The purpose of the research was to compare the state of Gnostic and balance abilities between different sports disciplines, in comparison with the control group. Methods: 80 probands of both genders, aged 18-30 years, were divided into 7 groups of 10, according to sports discipline. The last control group consisted of 10 probands who did not perform any sport. Active athletes were selected for the research, involved in the highest competition of their discipline from various sports: sprint, athletic walking, throws, long jumps, judo, basketball and ice hockey. For the diagnosis of gnostic functions, tests were chosen to examine the modalities of kinesthesia, somatognosis and stereognosis. To test the equilibrium functions, 6 tests using BOSU with both, visual and non-visual control were used. Results: Results at the level of statistical significance at the level of p = 0.05 were demonstrated between the groups of jumpers and basketball players in the kinesthesia test and in the somatognosis test between all athletes and the control group. The stereognosis test showed significant differences between all groups except the sprinter and basketball players. In the equilibrium tests, a statistically significant difference was shown only in the test of standing on both lower limbs without visual control, between the groups of sprinters and the control group, sprinters and basketball players and between the control group and all athletes together. Conclusions: Based on the results, we can say that there are significant differences in some proprioceptive and equilibrium modalities in different sports. We assume that the type of sport can have an impact on the quality of these functions DOI: https://doi.org/10.24040/sjss.2020.6.2.4-14